A Compact Dielectric Resonator Antenna Excited by a Planar Monopole Patch for Wideband Applications - Xuping Li; Yabing Yang; Fei Gao; Hanqing Ma; Xiaowei Shi (International Journal of Antennas and Propagation)
A compact dielectric resonator antenna (DRA) suitable for wideband applications is presented in this paper. The proposed antenna is mainly composed by a notched cylindrical dielectric resonator (DR) coated with a metal surface on the top and a finite ground plane where the presented DR is placed. This antenna is very simple in structure and has a very low overall height of 0.14λmin at its lowest operation frequency. A comprehensive parametric study is carried out based on Ansoft HFSS to optimize the bandwidth. The proposed antenna has been successfully simulated, optimized, fabricated, and measured. The measurement results demonstrate that the proposed design produces an impedance bandwidth of more than 75%, ranging from 2.9 GHz to 6.7 GHz for the reflection coefficient less than −10 dB. In particular, consistent broadside radiation patterns, stable gain, and high radiation efficiency are also obtained within the operation frequency band.